Characterization of C-S-H gels by pair distribution function analysis - García-Aranda, Miguel Ángel (My University, 2021)
Portland cement (PC) is the most manufactured world product. However, cement industry is one of the major contributors for greenhouse gas emissions. On average, for every ton of grey PC clinker, around 0.87 CO2 tons are released into the atmosphere. Alternative cements showing similar performances to ordinary PC are needed. A recent work [1] commissioned by the United Nations Environment Program Sustainable Building and Climate Initiative has identified the use of supplementary cementitious materials (SCMs) as the most favourable approach for lowering CO2 emissions in the cement industry. In order to develop more sustainable cements, the hydration products must be well understood which is far from straightforward. The hydration reactions of tricalcium silicate, Ca3SiO5 (main phase of PC) consist of its dissolution, the formation of the nanocrystalline calcium-silicate-hydrate (C-S-H) gel, jointly with the crystallization of portlandite, Ca(OH)2 according to equation (1). C-S-H gel seems to be composed by defective nanocrystalline clinotobermorite, amorphous (a few layers thick) Ca(OH)2 and gel pore water [2].
Keywords: Química inorgánica; Cristalografía; Cemento; cements; synchrotron; local structure; Cemento